Financial Development and Economic Growth Nexus: The Moroccan Case - Abouch, Mohamed; Ezzahid, Elhadj (UI Scholars Hub, 2011)
The issues of the existence and the direction of causality between inance and growth are not yet settled. Even if theoretical and historical evidences suggest an important contribution of inance to foster economic growth, empirical studies provide conlicting results depending upon analytical approaches, econometric techniques, and used data sets. The empirical exploration of the links between the development of the Moroccan inancial sector (MFS) and the economic performance of the country shed some light on the proile of this relationship. It appears that even if the indicators measuring the degree of development of the MFS have steadily evolved, they are not systematically and signiicantly linked with economic growth. This situation may be explained by the characteristics of the MFS and the existence of other factors, not related to this sector, that hinder economic growth.